Finite element analysis bending of composite sandwich beams with metal facesheets - Rhuban S/O Jeva (Nanyang Technological University, 2024)
This study investigates the structural bending behaviour of the sandwich composite beams with the use of face sheet metals. Three-Point bending was used to analyse the bending behaviour. Finite Element Analysis (FEA) was used to simulate past experimental studies of such bending. Past experimental results were analysed and used to validate the FEA simulated results. ANSYS, an engineering simulation and 3D design software was used to perform FEA. Unifoam Polystyrene Foam was the material in interest for this study. This Foam acts as the core and is sandwiched between two aluminium face sheets. Various FEA models were simulated to find the optimal model that possessed the characteristics of allowing the analysis to be more efficient, simple as well as capable of maintaining a high level of accuracy overall. A total of four specimens with different dimensions and configurations were modelled and evaluated – Specimen 1, 2, 3 and 4. The first two specimens – Specimen 1 and 2, consisted of two core materials of varying thickness. These specimens were cross-referred with past experimental data and FEA analysis which made use of identical materials. Specimens 3 and 4 were face sheet metals sandwiching the core with varying thickness. Past FEA was used to evaluate the results of the two specimens. The analysis showed that cores sandwiched with face sheet metals had a higher flexural stiffness compared to just the core alone. Moreover, increasing the thickness of the core increased the force needed to bend. It also showed that the FEA results recorded higher forces compared to the experimental ones at the midsection of the specimens. Non-linear characteristics of the experimental study was not proven in this study. However, it did show similar linear elastic behaviour to previous studies that were conducted. However, an additional study that was conducted using a different core material was able to prove the non-linear region of the analysis. Poly Vinyl Chloride (PVC) Foam was able to prove the non-linear region of the analysis. In addditon, Ansys Composite PrePost (ACP) was studied to examine its applicability in such structures. Unfortunately, the ACP works well only with thin structures. Overall, the study did show that in order to simulate real-life conditions, the database has to be provided with sufficient and accurate parameters.